Distributed photovoltaic solar system architecture with single‐power inductor single‐power converter and single‐sensor single maximum power point tracking controller. Issue 10 (1st October 2014) - Abu Qahouq, Jaber A.; Jiang, Yuncong
Abstract : This study presents a distributed photovoltaic (PV) solar system architecture with a single‐power inductor, single‐power converter and single maximum power point tracking (MPPT) controller that only requires one sensor. This PV architecture is able to perform MPPT for a multichannel distributed PV system at panel level, cell group level and/or single cell level under mismatching and partial shading conditions. The single power stage is a multiple‐input single‐inductor boost power converter which operates in continuous conduction mode. This work targets the high‐cost and high‐complexity issues of module integrated converter (MIC) and sub‐MIC PV architectures, which affect their practicality in many applications. The concept and operation of the single‐power‐converter single‐controller single‐sensor MPPT architecture is presented, analysed and verified by results obtained from a proof‐of‐concept experimental prototype.